The South African administrative powers of the Commissioner for Inland Revenue, taxpayer's procedural remedies and the impact of the Constitution (Act 200 of 1993) thereon - Mzenze, Sibongiseni (Department of Commercial Law, 2023)
Income Tax Act (Act No 58 of 1962) imposes a tax called normal tax upon taxpayers. The extent of the taxpayer's liability must be assessed, that is, determined authoritatively by the Commissioners for Inland Revenue. This dissertation utilises the administrative powers of the Commissioners; taxpayer's procedural remedies, preservation of secrecy and the impact of the Constitution thereon. Now that we are a constitutional state, this paper seeks to examine whether our constitution accommodates the vast discretionary powers of the Commissioner' preservation of secrecy, appeals and reviews against Commissioner's decisions. Alternatively, do powers of the Commissioner in terms of the Income Tax Act measure up with the expectations and needs of the Constitution? What are constitutional restrictions, if any, are there on the exercise and implementation of the taxpayer's procedural remedies? Are the provisions of sections 4(1) and 80 of the Income Tax Act consistent with the Constitution? The South African Transitional Constitution (Act 200 of 1993) embodies a Bill of Rights which will have an impact on tax law. This makes it imperative that a "rights culture" be engendered in all the people of South Africa.